Multimodal Synergistic Strategies for Diabetic Wound Healing Using Glucose Oxidase Nanocomposites: Therapeutic Mechanisms and Nanomaterial Design - Fan Z; Liang C; Zhang J; Li Y; Tan L; Deng H; Wang P; Wang J; Kang J; Zhu Y; Fu H; Tao J (International Journal of Nanomedicine)
Zaiwei Fan,1,* Chengzhi Liang,1,* Jiayu Zhang,2,* Yiming Li,3,* Lihua Tan,1 Hui Deng,1 Pinkai Wang,1 Jialiang Wang,1 Jiawei Kang,1 Yudan Zhu,1 Hang Fu,1 Jun Tao1 1Department of Orthopedics, The Second Affiliated Hospital, Jiangxi Medical College Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China; 2Department of ECG, Sir Run Run Shaw Hospital, Sir Run Run Shaw Institute of Clinical Medicine of Zhejiang University, Hangzhou, People’s Republic of China; 3School of Traditional Chinese Medicine, Nanchang Medical College, Nanchang, Jiangxi, 330052, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Tao, Department of Orthopedics, The Second Affiliated Hospital, Jiangxi Medical College Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China, Email ndefy14038@ncu.edu.cnAbstract: Diabetic wounds (DWs) are characterized by high blood glucose levels, and one of the primary strategies for regulating blood glucose is the use of glucose oxidase (GOx). This enzyme catalyzes the oxidation of glucose to produce D-gluconic acid, consuming oxygen and generating hydrogen peroxide (H₂O₂) in the process. In DWs, this reaction not only effectively reduces glucose concentrations at the wound site but also provides an antibacterial effect through the release of H₂O₂. Based on this principle, combining glucose oxidase with other therapeutic approaches to develop multimodal wound treatment strategies has garnered significant research attention. Additionally, the abundance of binding sites on the GOx molecular surface enables the construction of multifunctional GOx-based nanocomposites. This review uniquely integrates emerging nanomaterial designs with cascade therapeutic strategies, offering insights into overcoming challenges in diabetic wound healing. Recently, multifunctional nanocomposites have gained attention for integrating multiple therapeutic modalities, relying on cascade mechanisms of multimodal synergistic therapies to tackle complex challenges in DWs treatment. However, there is currently no systematic review that comprehensively elaborates on the construction of these nanocomposites and the specific applications of multimodal treatment strategies in DWs healing. To fill this gap in the field, this review provides a comprehensive overview of these nanomaterials, starting with a systematic exploration of cascade and synergistic therapeutic mechanisms centered on GOx-catalyzed reactions. It highlights applications in photothermal therapy (PTT), photodynamic therapy (PDT), and gas therapy (GT), summarizes the design of nanocarriers, and discusses challenges in DWs healing and future development directions. The findings discussed provide a pathway for the development of clinically viable, cost-effective therapies for chronic wounds.Keywords: glucose oxidase, wound healing, synergistic strategies, nanocomposite, diabetic wounds